Analisis Implementasi Perencanaan Sarana dan Prasarana Pendidikan di MIS Nurul Fadhilah - Nur Alfiana Kholizah; Fathia Hanifah; Tarisa Munawwarah; Dinda Aulia Sani; Intan Savitri; Rizki Akmalia (Journal on Education, 2023)
In an instructive organization, offices and frameworks are important parts. Managers of educational institutions are obliged to maintain their facilities and infrastructure. Facilities and infrastructure in this case are aspects that support the success of the teaching and learning process as well as the efficiency and effectiveness of all school activities. In addition, it is important for educational institutions to provide public services to increase community response and student satisfaction. It is undeniable that the completeness of these facilities will increase parents' trust in the school, and students will also be enthusiastic in every learning process. Facilities and infrastructure can also increase the potential for student enthusiasm for learning well. Through research using subjective strategies and interview procedures, the analysts state observable facts related to the office and foundation at MIS Nurul Fadhilah where the office and framework in the school are towards the culmination and perfection of interaction for this.